(untitled) (Research, Society and Development, 2021)
The consensual model of conflict resolution has gained prominence in Sanctioning Law, whether in its criminal or administrative aspects. The recent amendment to Article 17, §1 of Law No. 8.429/1992, which now admits the civil non-prosecution agreement, is in line with a national and international trend of overcoming the dogma of the legal impossibility of agreements in conflicts involving the Public administration. The innovation conveys relevant progress in the fight against corruption, in the perspective of faster and more efficient results in cases involving administrative misconduct, whose resolution was not satisfactory by the exclusive method of misconduct action. The present study aims to contribute to the construction of guidelines that allow filling the gap left by the legislator regarding the mode of operationalization of the agreement (elements, conditions, limits, etc.), considering that the legal provisions that disciplined material aspects -al and procedural aspects of the agreement were vetoed by the President of the Republic. For that, the inductive method will be used, from the examination of legal norms, bibliographical and jurisprudential research.